Diversity and biofertilizer potential of root endophytic fungi in Arabica coffee - SOFYAN SOFYAN; ADE ROSMANA; NASARUDDIN NASARUDDIN; HARIS BAHRUN; KURNIAWAN KURNIAWAN; AKHMAD SYAKUR; DARMAWAN RISAL (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Sofyan, Rosmana A, Nasaruddin, Bahrun H, Kurniawan, Syakur A, Risal D. 2025. Diversity and biofertilizer potential of root endophytic fungi in Arabica coffee. Biodiversitas 26: 5977-5988. Sustainable Arabica coffee cultivation requires eco-friendly biological inputs to improve plant growth and soil quality. This study explored the diversity and physiological potential of root endophytic fungi isolated from Arabica coffee plants at two age-structured plots within one village in Maros, South Sulawesi, Indonesia, and evaluated their capacity to quantify phytohormone-related signals and assess compost enrichment. Endophytic fungi were isolated from coffee roots and characterized morphologically to the putative genus level, while biochemical assays estimated IAA-equivalents and GA-like (GA3) compounds. A randomized block design was used to assess compost decomposition and biofertilizer responses of Arabica seedlings in non-sterile soil. Results showed that a total of fourteen isolates were obtained, with Trichoderma spp. dominating young roots (<3 years) and Aspergillus, Penicillium, and Paecilomyces more common in older roots (>10 years). Isolate 5C10BM produced the highest IAA-equivalent signal (3.02 ppm), while P11 yielded the highest GA-like signal (8.14 ppm) and showed a trend toward higher compost nitrogen content relative to the uninoculated control. Compost analysis showed that isolate 6C10BM increased C-organic (20.07%), isolate 11C3BM showed nitrogen levels of 1.19% and isolate 14C3BM elevated phosphorus (0.63%) and potassium (0.42%). Plant assays revealed that isolate 2C10BM increased seedling height (45.4 cm), whereas 9C10BM enhanced leaf number and area. The study demonstrates functional diversity among endophytic fungi, with strain-specific capabilities, particularly in isolates 5C10BM, 11C3BM, and 14C3BM, which exhibited indicative traits relevant to biofertilizer and compost-activating potential. These findings provide insights into endophyte-associated functional traits; future work will include molecular identification and verification of root colonization.